Development of Entrepreneurial Independence Attitudes for Santri (Case Study at Adh Dhuhaa Islamic Boarding School in Baki District, Sukoharjo Regency) - Nuryanti, Lilis; Widodo, Joko; Murwatiningsih, Murwatiningsih (Journal of Economic Education, 2018)
The attitude of independence for students in Islamic boarding schools is a value manifested in behavior (attitude) that is formed through entrepreneurial practice activities. One aspect that encourages the success of students in developing an attitude of independence is called entrepreneurship education. This research approach was qualitative with descriptive analysis method, one of them with a case study. The objective of the research are 1) to describee and analyze the curriculum design of boarding school. 2) to describe and analyze learning methods in Islamic Boarding School. 3) to describe and analyze the development of entrepreneurial independence attitudes for students. The result of the study are: 1) there is no entrepreneurship curiculum at Islamic boarding school, but the students directly go to the field to doing practice; 2) entrepreneurship learning methods are delivered directly by teachers to the students; 3) the development of students independence attitude includes discipline, honesty, responsibility, action-oriented.